Political Ecology of Sasi Laut: Power Relation on Society-Based Coastal Management - Mony, Ahmad; Satria, Arif; Kinseng, Rilus A (Journal of Rural Indonesia [JORI], 2015)
The coastal resources management cannot be separated from the power relation of all stakeholders with their interest on beneficial aspects. Some stakeholders may have similar interests, and some others have the dif- ferent ones with their own strategies in terms of meeting their interests. This kind of relation may take place in some forms, such as direct confrontation, physical resistance, persuasion, or collaboration. It may also be in the form of single form, yet flexible and dynamic, depends on the local and national politic situation. The existence of sasi laut is included in power relation dynamics with its own effects. The result of the study shows that the effect of this power relation, both in internal and external levels, tends to weaken the sasi laut. The power relation in the form of confrontation and physical resistance decreased the society compliance as well delegitimized the authorized boards. In contrast, the collaborative relation with external stakeholder like non-governmental organizations, universities, and donor organizations not only strengthened the capacity of the NGO and their organizations, this relation also would result in such centralized figures and empow- erment capitalization in which weakens the sasi laut application.Keywords: coastal resources, sasi laut, power relation, centralized figures, empowerment capitalization